(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sudden change in the brightness and color values in the images causes introduction of noise in image and frames of the video stream. Such random variation of the brightness and color values doesn’t carry any intelligence in fact, it deteriorates the quality of the image and frames in video stream. To nullify the effect of such meaningless information, denoising frameworks are designed. In this research paper we have proposed denoising framework for speckle noise, this approach is sometimes also called as de-speckling algorithm. For performance evaluation we are critically analyzing the de-speckling techniques with respect to the PSNR, MAE, and MSSIM.